Proton pump inhibitors versus histamine-2 receptor antagonists for stress ulcer prophylaxis during extracorporeal membrane oxygenation: a propensity score-matched analysis - Hiroki Matsui; Hideo Yasunaga; Hiroshi Tanaka; Yutaka Kondo; Hiroyuki Ohbe; Kiyohide Fushimi (BMJ Open)
Purpose Patients receiving extracorporeal membrane oxygenation (ECMO) generally receive proton pump inhibitors (PPIs) or histamine-2 receptor antagonists (H2RAs) to avoid major gastrointestinal bleeding. Our aim was to compare outcomes between patients receiving PPIs and H2RAs for stress ulcer prophylaxis during ECMO.Materials and methods We performed a retrospective cohort study using the Japanese Diagnosis Procedure Combination Database, using data recorded from 1 July 2010 to 31 March 2017. We defined patients who received PPIs within 2 days after starting ECMO as the PPIs group and those who received H2RAs within 2 days after starting ECMO as the H2RAs group. We performed propensity score matching to compare outcomes. The primary outcomes were gastrointestinal bleeding requiring endoscopic haemostasis and in-hospital mortality. The secondary outcomes were red blood cell transfusion, hospital-acquired pneumonia and Clostridium difficile infection during hospitalisation.Results Of 11 328 eligible patients, 9738 received PPIs and 1590 received H2RAs. Propensity score matching created 1556 pairs. No significant differences were seen regarding endoscopic haemostasis (1.2% vs 0.8%; p=0.37), in-hospital mortality (53.0% vs 53.1%; p=0.94), red blood cell transfusion rates (91.4% vs 89.7%; p=0.11), hospital-acquired pneumonia (13.0% vs 12.4%; p=0.59) or C. difficile infection (0.1% vs 0.2%; p=0.32) between the PPIs and H2RAs groups, respectively.Conclusion We found no differences in the evaluated outcomes between the PPIs and H2RAs groups. Both PPIs and H2RAs are treatment options for stress ulcer prophylaxis in patients undergoing ECMO.